Logotherapy to Increase Self-Esteem in Emerging Adulthood with Nomophobia - Nadeak, Esrawati Ulina; Astuti, Kamsih (Bulletin of Counseling and Psychotherapy, 2024)
Self-esteem is an individual’s evaluation of themselves related to the belief that they have abilities, accomplishments, importance, and worth. Low self-esteem in emerging adulthood can lead to various problems and maladaptive behaviors, one of which is nomophobia. This study aims to determine the effect of logotherapy on self-esteem in emerging adulthood with nomophobia. This study used the experimental design untreated control group design with dependent pre-test and post-test samples. The study subjects were 12 emerging adulthood aged 18 to 29 years with nomophobia, with self-esteem scores in the medium category. Subjects were divided into 2 groups, consisting of 6 experimental groups and 6 control groups. The experimental group was given an intervention in the form of logotherapy in 6 sessions with 2,5 to 3 hours in a meeting. The data analysis method used is the Mann-Whitney U Test and Wilcoxon Signed Rank Test. Based on the results of the Mann-Whitney U Test, the value of Z = -2.166 was obtained, with p<0.05, meaning that there was a difference in self-esteem scores in the control group and the experimental group before being given logotherapy. Meanwhile, based on the Wilcoxon Signed Rank test, the value of Z = – 2.207 was obtained, with p<0.05, meaning that there was a difference in self-esteem scores in the experimental group between measurements before and after being given logotherapy, where the self-esteem of the experimental group after being given logotherapy (mean = 77.67) was higher than before being given logotherapy (mean = 68.83). These results indicated that logotherapy could improve self-esteem in emerging adulthood with nomophobia.